EQUALITY OF POSSIBILITIES AND TREATMENTS IN THE VIEW OF EMPLOYMENT AND OCCUPATION - Brković, Radoje; Vučinić, Dejan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
This paper analyzes international standards relating to discrimination in terms of employment and occupation, which are primarily contained in the legal instruments of the International Labor Organization. The above standards contain, in the first place, the Convention no. 111. and Recommendation no. 111 from 1958, as well as Convention no. 100. and Recommendation no. 90. relating to the equal rewarding of male and female labor force.The aspect of application, that is, the problems and obstacles that arise in the application of international standards related to the issue of discrimination in employment and occupation and the equal rewarding of the male and female labor force for equal work, more precisely, work of equal value, will be analyzed in particular.
Keywords: discrimination in employment and occupation; equal rewarding of male and female labor force; Convention no. 111 and no. 100; Recommendation no. 111 and no. 90; application